(a³+b³+3b²+3b+1)/(a²-ab-a+(b+1)² при a=4-корень из3, b=4+корень из 3. Помогите пожалуйста, очень надо

(a³+b³+3b²+3b+1)/(a²-ab-a+(b+1)² при a=4-корень из3, b=4+корень из 3. Помогите пожалуйста, очень надо
Гость
Ответ(ы) на вопрос:
Гость
a³ +b³ +3b² +3b+1  = a³ + (b³+3b²+3b+1) =        a³ + (b+1)³        = a²-ab-a+(b+1)²             a² -(ab+a)+(b+1)²     a² - a(b+1) + (b+1)² = (a+b+1) (a² - a(b+1) + (b+1)²) =  a+b+1       a² - a(b+1)+(b+1)² При а=4-√3        b=4+√3 a+b+1=4-√3+4+√3+1=4+4+1=9 Ответ: 9
Не нашли ответ?
Ответить на вопрос
Похожие вопросы